Copolymerization of ethylene and non-conjugated diene with metallocene/methylaluminoxane system supported on MCM-41 mesoporous material - Lopes, D. E. B. (2013)
Ethylene was copolymerized with the non-conjugated diene 5,7-dimethylocta-1,6-diene by metallocene catalysts, homogenous and supported on MCM-41 mesoporous material activated by methylaluminoxane at room temperature. The employed metallocenes were (BzCp)2ZrCl2 (1), (C18H37Cp)2ZrCl2 (2), (CH3)2Si(Ind)2ZrCl2 (3) and /2C(Cp,Flu)ZrCl2 (4). Diene incorporation and thermal characteristic of the polymers were determined by 13CNMR and DSC. For the homogeneous systems, only the unbridged metallocene (1) showed a decrease in the activity as the diene content was increased. The ability for diene incorporation in the polymer chain followed the catalyst order (1) < (3) < (2) < (4). Regarding the supported systems, it was observed that all of them showed lower activity than the corresponding homogeneous catalysts. A sharp loss of activity in relation to the homogeneous counterpart was noticed by employing the ansa-metallocenes on MCM-41, especially the complex (4) supported catalyst. The effect of the mesoporous material as support on the behavior of the studied metallocene homogeneous systems in ethylene–diene copolymerization was an increase of polymer molecular weight, maintaining the same level of diene incorporation, except for catalyst (2), when a decrease of the diene incorporation was observed.